Farmers’ purchase intention and willingness to pay for certified sweetpotato seed under different disease pressure zones in Uganda - Musoke, Charles; Kyazze, Florence B.; Kibwika, Paul; Mukasa, Settumba B. (Wiley, 2024)
The use of certified sweetpotato (Ipomoea batatas) seed (CSS) was reported to unlock the yield potential of the crop leading to an over 80% yield increase. Despite the availability of elements of a formal CSS system, uptake in Uganda has remained dismal. Interdependence between farmer knowledge, perceptions, and purchase behaviors (PBs) is not well understood in a way that could allow the design of meaningful policies and interventions. This study aimed at unveiling factors underlying PB through purchase intention (PI) and willingness to pay (WTP) by interviewing 289 farmers from Omoro and Mpigi districts in Uganda, representing the low and high virus disease pressure zones, respectively. A modified theory of planned behavior (TPB) incorporating awareness as independent and farmer innovativeness as mediating variables expounded the relationships. Data were collected on perceptions, knowledge, innovativeness, and PI using a five‐point Likert scale plus WTP as a price, subjected to descriptive and structural equation modeling analysis. Results indicated significant locational differences in most socioeconomic characteristics. Middle income, CSS information access, and farming experience of 7–30 years conferred more likelihood of high PI. Conversely, high PI, group membership, and being female and middle‐aged increased the likelihood of high WTP. The effects of attitude, perceived behavioral control, and awareness were significant in high disease zone, while subjective norm was significant across disease zones. PI significantly affects WTP in high disease zone (p = 0.000) but its effect is insignificant in low disease zone (p = 0.569). An interplay of socioeconomic, perception, and knowledge attributes influences CSS PB calling for social marketing strategies with location‐specific interventions.